Al-Ghazali’s framework of teachings professional values: analyzing the pedagogical principles in Islamic education - Jalaldeen, Jemeela; Al-Hidabi, Dawood Abdulmalek Yahya (IIUM Press, 2025)
Values are a cornerstone of education, serving as essential guides for the learning process. This article investigates the pedagogical principles articulated by Imam Ghazali, one of the most influential Muslim scholars of the 11th century, particularly as presented in his seminal work, "Ihya' Ulum al-Din." The study offers a comprehensive analysis of Ghazali's unique approach to teaching, which integrates ethical and spiritual dimensions aimed at character development, ethical conduct, and spiritual growth. Key values such as sincerity, humility, empathy, and justice are identified as fundamental to the educational experience within his framework. The relevance and application of Ghazali's ideas in contemporary educational settings, particularly in Islamic schools and institutions, is emphasized. Employing a qualitative methodology, this study utilizes textual analysis of Ghazali's works alongside secondary literature to deeply understand his pedagogical model. The findings indicate that Ghazali's focus on ethical and spiritual education provides a robust framework that is vital for addressing contemporary educational challenges in the Muslim world